Evaluation of Yogurt Drink Quality at CV Violla Foods Yogyakarta as a Requirement for Registering the Distribution Permit on Food and Drug Control Agency (BPOM) - Tiyas Tono Taufiq; Agustina Agustina (Jurnal Sains dan Teknologi Pangan, 2023)
Yogurt drink is one of the processed dairy products which is categorized as a product with a high level of risk by the Food and Drug Control Agency (BPOM) so its distribution must meet the requirements and be directly supervised by BPOM. To obtain a Distribution Permit Number (NIE), yogurt drink products must meet the quality requirements set by BPOM including the amount of non-fat solid, protein content, total Enterobactericiae and Salmonella contaminants, and total minerals contaminants, including Arsenic (As). Lead (Pb), Mercury (Hg), Cadmium (Cd), and Tin (Sn). This study aims to determine the quality of the yogurt drink produced by CV Violla Foods against the BPOM distribution permit requirements. From the results of this evaluation, it can be seen that the parameters for contamination of tin (Sn) are still outside of the limits, while all other requirements have met the standards. Action is required from the company to ensure that all parameters, including Sn contamination, meet the standards through evaluation of raw materials and production processes, to be followed up with re-testing of products to be registered.